2009
DOI: 10.1186/1751-0147-51-28
|View full text |Cite
|
Sign up to set email alerts
|

Computer tomographic investigation of subcutaneous adipose tissue as an indicator of body composition

Abstract: BackgroundModern computer tomography (CT) equipment can be used to acquire whole-body data from large animals such as pigs in minutes or less. In some circumstances, computer assisted analysis of the resulting image data can identify and measure anatomical features. The thickness of subcutaneous adipose tissue at a specific site measured by ultrasound, is used in the pig industry to assess adiposity and inform management decisions that have an impact on reproduction, food conversion performance and sow longevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Because meat quality measurements are measured only on dressed carcasses, this necessitates the identification and implementation of ways to determine meat quality in live animals. To this end, non-invasive methods, such as ultrasonic backfat thickness measurements (Turner et al, 1990), video image analysis (McClure et al, 2003), magnetic resonance imaging (Monziols et al, 2005) and computer tomography (McEvoy et al, 2009) have been used to determine carcass fat content in live animals.…”
Section: Introductionmentioning
confidence: 99%
“…Because meat quality measurements are measured only on dressed carcasses, this necessitates the identification and implementation of ways to determine meat quality in live animals. To this end, non-invasive methods, such as ultrasonic backfat thickness measurements (Turner et al, 1990), video image analysis (McClure et al, 2003), magnetic resonance imaging (Monziols et al, 2005) and computer tomography (McEvoy et al, 2009) have been used to determine carcass fat content in live animals.…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of nondestructive BCA methods have been developed, each with its advantages and shortcomings, such as air-displacement plethysmography (ADP) (6), bioelectrical impedance analysis (BIA) (7), dual-energy x-ray absorptiometry (DXA) (8), total-body electrical conductivity (TOBEC) (9), total body potassium (TBK) (10), isotope dilution (11), skin-fold thickness measurements (SFT) (12), multicompartment models (13), computed tomography (CT) (14), MRI (15), magnetic resonance spectroscopy (MRS) (16), and quantitative magnetic resonance (QMR) (17).…”
mentioning
confidence: 99%
“…Secondly, the L2 level is of particular interest in the pig because the P2 site, a commonly used site in the pig industry to measure SAT thickness by ultrasonography, is located on this slice. McEvoy et al ( 19 ) indicated that the current P2 site is situated in an area of low local variation and optimal correlation with the total volume of SAT. Finally, it is easier to delineate manually the RAT after identification of the kidneys that are clearly visible at the L2 level in the pig.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement site was localised by palpation on the left flank, approximately 6–7 cm lateral to the dorsal spinous process at the level of the most caudal point of the last rib (Fig. 2), which corresponded to the P2 site used in the pig industry ( 19 ) . After contrast optimisation (C4), the grey-scale image was frozen and transferred to ImageJ software for further analysis.…”
Section: Methodsmentioning
confidence: 99%